Association Between Leukocyte Mitochondrial DNA Copy Number and Non-alcoholic Fatty Liver Disease in a Chinese Population Is Mediated by 8-Oxo-2′-Deoxyguanosine - Ma, Chifa; Liu, Yiwen; He, Shuli; Zeng, Jingbo; Li, Pingping; Ma, Chunxiao; Ping, Fan; Zhang, Huabing; Xu, Lingling; Li, Wei; Li, Yuxiu (Frontiers in Medicine, 2020)
Abstract Background: Alterations in mitochondrial DNA are potentially associated with oxidative stress, and may be involved in the pathogenesis of non-alcoholic fatty liver disease (NAFLD). However, the association between mitochondrial DNA copy number (mtDNAcn) and NAFLD was not consistent. In addition, the association between inflammation and NAFLD has not been established yet. The present study, based on a Chinese population of individuals with different glucose statuses aimed to explore the association between leukocyte mtDNAcn, markers of oxidative stress, as well as inflammation and NAFLD. Materials and Methods：A total of 318 participants from a diabetes project were included. NAFLD was diagnosed by ultrasonography. Leukocyte mtDNAcn was determined by PCR assay. The levels of the inflammation markers tumor necrosis factor-α (TNF-α) and interleukin-6 (IL-6) and the oxidative stress markers glutathione reductase (GR), superoxide dismutase (SOD), and 8-oxo-2′-deoxyguanosine (8-oxo-dG)]were also measured. Results: Participants with NAFLD (n=105) exhibited significantly higher leukocyte mtDNAcn, IL-6, and 8-oxo-dG (all P<0.05). Pearson correlation analysis indicated mtDNAcn was negatively associated with age, uric acid, SOD, and TNFα, but was positively associated with 8-oxo-dG (all P<0.05). Univariate logistic regression analysis revealed that mtDNAcn was positively associated with NAFLD (OR=1.617, 95% CI: 1.036 to 2.525; P=0.034). However, after adjustment for 8-oxo-dG, this association was no longer statistically significant (OR = 1.534, 95% CI:0.979 to 2.403, P=0.062). Moreover, the stress marker 8-oxo-dG was independently associated with NAFLD after adjustment for mtDNAcn, IL-6, glucose tolerance status and other conventional NAFLD risk factors(OR=1.707, 95% CI: 1.142 to 2.550, P=0.009).Mediation analysis indicated that 8-oxo-dG fully mediated the effect of mtDNAcn on the incidence of NAFLD(direct effect β=0.5221,95%CI: -0.0648 to 1.2504; indirect effect β= 0.0946, 95% CI: 0.0049 to 0.2463). Conclusions: In a Chinese population, the association between leukocyte mtDNAcn and NAFLD was fully mediated by high levels of 8-oxo-dG. Thus, oxidative stress may be an important driver of NAFLD, and clinical interventions aimed at decreasing oxidative stress to improve NAFLD warrant further research.